A Lifestyle Medicine Clinic in a Community Pharmacy Setting - Thomas L. Lenz; Jessica Skradski; Maryann Z. Skrabal; Liz Ferguson; Michael S. Monaghan (University of Minnesota Libraries Publishing, 2010)
Chronic diseases continue to be a significant burden to the health care system. Pharmacists have been able to show that drug therapy for patients with chronic diseases can be improved through medication therapy management (MTM) services but have yet to become significantly involved in implementing lifestyle modification programs to further control and prevent chronic conditions. A novel and innovative lifestyle medicine program was started by pharmacists in a community pharmacy in 2008 to more comprehensively prevent and manage chronic conditions. The lifestyle medicine program consists of designing seven personalized programs for patients to address physical activity, nutrition, alcohol consumption, weight control, stress management, sleep success, and tobacco cessation (if needed). The lifestyle medicine program complements existing MTM services for patients with hypertension, dyslipidemia, and/or diabetes. This program is innovative because pharmacists have developed and implemented a method to combine lifestyle medicine with MTM services to not only manage chronic conditions, but prevent the progression of those conditions and others. Several innovative tools have also been developed to enhance the effectiveness of a lifestyle medicine program. This manuscript describes the program's pharmacy setting, pharmacy personnel, participants and program details as well as the tools used to integrate a lifestyle medicine program with MTM services. Type: Clinical Experience